Holy Scripture in the monothelite controversy. The Standpoint of Maximus the Confessor - Kashchuk, Oleksandr (Vox Patrum, 2018)
The position of Maximus the Confessor concerning the biblical argumentation in the dispute with Monotheletism consists in applying predominantly the literal approach to the interpretation of the New Testament. Since it was a Christological question, the New Testament played a substantial role. However, there are several instances of where Maximus applies allegorical and typological mode of interpreting the particular passages. Preferring the literal mode of interpretation may signify that Maximus sticking to the letter of the text avoided manipulating the inspired text with many variations in interpretation. Biblical argument is not sufficient on its own to be persuasive in theological discussion, therefore it requires additional support and explanation. That is why Scripture is not thought of as the sole authority for Christian faith. It is interpreted by Maximus with taking into account not only the teaching of the Fathers and the Councils but also the philosophical heritage. If the Fathers and Councils can not answer to the current theological question, the interpretation of Scripture should be collated with the teaching of the Holy See.